Evaluation of the management of optic neuritis: audit on the neurological and ophthalmological practice in the north west of England. Issue 1 (1st January 2002) - Ghosh, A; Kelly, S P; Mathews, J; Cooper, P N; Macdermott, N
Abstract : The management of acute optic neuritis by neurologists and ophthalmologists in the north west of England was assessed in the light of the Optic Neuritis Treatment Trial (ONTT) recommendations. A questionnaire on a fictitious case of typical unilateral optic neuritis was mailed to all consultant ophthalmologists and neurologists working in the North West and Merseyside Health Authorities. They were then asked to comment on management of the case. Fifty two out of 86 ophthalmologists and 20 out of 28 neurologists replied. The overall response rate was 63%. Sixty five per cent of neurologists and 46% of ophthalmologists would investigate a typical case of acute optic neuritis further. Forty six per cent of neurologists and 36% of ophthalmologists were likely to arrange MRI of the brain or orbit. Significantly more neurologists (55%) than ophthalmologists (9%) chose to treat with intravenous methylprednisolone (p<0.005). Significantly more ophthalmologists (64%) than neurologists (32%) chose not to give steroids (p<0.025). Oral prednisolone alone was rarely selected for treatment. Respondents were more likely to discuss multiple sclerosis with the referring doctor than with the patient. Only 32% of ophthalmologists and 20% of neurologists would clearly mention the possibility of improvement to the patient. Clear differences in practice between ophthalmologists and neurologists remain. A consensus on practice guidelines on the issues raised might be useful.